Intra-Operative Infrared Thermography of Ocular Surface During Cryodestruction of Epibulbar Tumours - Zadorozhnyy, Oleg; Buiko, Oleksandr; Pasyechnikova, Nataliya (Problems of Cryobiology and Cryomedicine, 2024)
The paper presents the possibilities of intraoperative use of infrared (IR) thermography to image the temperature distribution of the outer ocular surface during cryodestruction of conjunctival tumours with localization in the ciliary body projection to determine an individual freezing regimen. IR thermography was carried out using a portable device for infrared real-time thermography. Thermal fields were visualized, and the duration of cooling and warming of the structures of the outer ocular surface around the area of freezing, including the cornea, were recorded. It was found that intraoperative IR thermography during cryodestruction of epibulbar tumours in the projection of the ciliary body allows real-time noninvasive imaging of the temperature fi eld dynamics around the freezing zone, which can be used to select individual cooling exposure to reduce the risk of complications by avoiding excessive cooling of intraocular structures. It was also determined that IR thermography makes it possible to assess the individual dynamics of rewarming of the ocular tissues to the initial level if a repeated cycle of tumour cryodestruction is necessary. Probl Cryobiol Cryomed 2024; 34(1):045–053